The crucified apostle: essays on Peter and Paul - Wilson, Todd A.; House, Paul R. (Wissenschaftliche Untersuchungen zum Neuen Testament / 2, 2017)
Publisher's decription: Peter and Paul have fascinated Christians since the first century. Though often pitted against one another in scholarship and popular imagination, they respected one another. In seventeen essays the contributors probe enduring issues in ways that provide fresh insights. They strive to advance New Testament scholarship by addressing Peter and Paul's historical interaction, their intertextual exegesis, and Paul's view of Pastoral Theology. Their focus on intertextuality reflects Peter's and Paul's saturation in scripture and their focus on Jewish and Gentile relationships seeks to foster unity in church and culture